1998
DOI: 10.1080/004982598239498
|View full text |Cite
|
Sign up to set email alerts
|

In vitrobiotransformation of flavonoids by rat liver microsomes

Abstract: 1. Sixteen naturally occurring flavonoids were investigated as substrates for cytochrome P450 in uninduced and Aroclor 1254-induced rat liver microsomes. Naringenin, hesperetin, chrysin, apigenin, tangeretin, kaempferol, galangin and tamarixetin were all metabolized extensively by induced rat liver microsomes but only to a minor extent by uninduced microsomes. No metabolites were detected from eriodictyol, taxifolin, luteolin, quercetin, myricetin, fisetin, morin or isorhamnetin. 2. The identity of the metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
129
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(142 citation statements)
references
References 17 publications
10
129
3
Order By: Relevance
“…It is efficiently oxidized by microsomes from Aroclor 1254-induced rats but not from uninduced rats (Nielsen et al, 1998;Galijatovic et al, 1999), suggesting that Aroclor 1254 induces a P450 isoform not normally present in either human or rat liver.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is efficiently oxidized by microsomes from Aroclor 1254-induced rats but not from uninduced rats (Nielsen et al, 1998;Galijatovic et al, 1999), suggesting that Aroclor 1254 induces a P450 isoform not normally present in either human or rat liver.…”
Section: Discussionmentioning
confidence: 93%
“…Much less is known about the oxidative metabolism of the flavonoids, in particular in humans. Studies with liver microsomes from Aroclor 1254-induced rats demonstrate extensive oxidative metabolism of several flavonoids (Duarte Silva et al, 1997a;Nielsen et al, 1998). This oxidation may be mediated by CYP1A1, as supported by subsequent studies (Duarte Silva et al, 1997b;Doostdar et al, 2000).…”
mentioning
confidence: 91%
“…Hydroxylation is an example of phase I cytochrome P450 mono-oxygenase-dependent activities that may be involved in the metabolism of flavonols. Nielsen et al (1998) showed that microsomes prepared from normal and Aroclor-1254-induced rats were capable of hydroxylating certain flavonols and flavones. The requirement for the metabolic activity was that either one or no hydroxyl groups were present on the Bring.…”
Section: Discussionmentioning
confidence: 99%
“…Detection was at 370 nm. Samples dissolved in 100 Wl 75% aqueous acetonitrile containing 1% formic acid were analyzed using a slight modi¢cation of the method of Nielsen et al [2]. Metabolites were eluted with acetonitrile and water containing 1% formic acid at a £ow rate of 0.8 ml/min.…”
Section: Hplc and Isolation Of Metabolites By Hplcmentioning
confidence: 99%
“…They have been considered inert and non-essential for human health; however, in the last few years it has been shown that £avonoids a¡ect a wide variety of biological systems in mammals, exhibiting antioxidant, anti-in£ammatory, antiviral, antiproliferative, and anticarcinogenic e¡ects [1]. Studies show that several £avonoids can inhibit or activate the cytochrome P450 (CYP) enzyme system in vitro and in vivo [2,3]. Recently in animal studies much attention has been paid to the antioxidant properties and the inhibitory role of £avo-noids in various stages of tumor development.…”
Section: Introductionmentioning
confidence: 99%